Paul's Inconsistency on the Jewish Law : A Stoic Ethical Perspective - Wilson, Annalisa Phillips, (Ancient Philosophy & Religion ;, 2022)
Paul's inconsistency on the Jewish law is a persistent scholarly problem. He can argue vociferously against circumcision but also acknowledge its potential benefit. He expresses pride in his ancestral law and practices, but also describes them in terms of slavery, curses, and rubbish. What are we to make of this? In this volume, Annalisa Phillips Wilson offers a fresh approach. Her comparison of Paul's texts with Stoic ethical reasoning demonstrates that his discourse on Jewish practices reflects Stoic discourse patterns on neutral selections and activities, discourse designed to establish one category of incommensurable worth.